2016
DOI: 10.1016/j.genhosppsych.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of back pain and its relationship with depression, psychosis, anxiety, sleep disturbances, and stress sensitivity: Data from 43 low- and middle-income countries

Abstract: Our data establish that BP is associated with elevated mental health comorbidity in LMICs. Integrated interventions that address back pain and metal health comorbidities might be an important next step to tackle this considerable burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
107
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 52 publications
(52 reference statements)
7
107
2
8
Order By: Relevance
“…Elbinoune et al 24 found that depression and anxiety were prevalent in individuals with chronic neck pain, and that these disorders were related to pain intensity. Also, Stubbs et al 25 noted that any type of back pain, together with chronic pain in this region, are associated with an increased risk of anxiety, as well as depression and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elbinoune et al 24 found that depression and anxiety were prevalent in individuals with chronic neck pain, and that these disorders were related to pain intensity. Also, Stubbs et al 25 noted that any type of back pain, together with chronic pain in this region, are associated with an increased risk of anxiety, as well as depression and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…While much of the research into psychiatric symptoms and chronic clinical conditions is centered on depression, with apparently significant associations between these conditions being identified, there is growing evidence that anxiety also coexists with such chronic conditions, and furthermore, coexists with their complications and vice versa 17,25 . Bener et al 27 observed a significant association between psychological stress and low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the condition of one can exacerbate the other. Chronic pain patients with depression are more likely to have higher severity and longer duration of pain, and the presence of pain is associated with increased depressive symptoms and possible relapses [4][5][6][7] . The detailed epidemiological information about the comorbidity of pain and depression was reviewed by Bair et al, (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Comparability across studies would be enhanced by use of standardised PA and SB questionnaires designed for use, and validated, with adults with mental illness. Medical comorbidities may influence engagement in PA and SB through pain and mobility restrictions 353,354 . Further, some psychiatric medications have side-effects, such as sedation, cognitive impairment, and emotional flattening 11,12 , which may influence PA and SB.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, medical comorbidities may affect PA barriers, preferences and enablers due to pain and mobility restrictions 353,354 . Medications and medical comorbidities were not assessed in this study, so it is unknown how they may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%